Public development banks and credit market imperfections (2016)
Which projects/firms should be the target of lending by a Public Development Bank (PDB)? What is the optimal design for the PDB's loans, and the optimal structure for delivering them? We analyze these questions in the context of a model where screening is costly to banks and underprovision of credit results from the inability of banks to appropriate the full benefits of projects they finance, more pronounced for high value projects. PDB intervention arises as a natural alternative to alleviate this inefficiency, since it originates in a failure in the private provision of credit. Lending to commercial banks at subsidized rates or providing credit guarantees, targeting the firms that generate high added value, are valid policy alternatives. Though in normal times PDB lending and credit guarantees are shown to be equivalent, lending is preferred when banks are facing a liquidity shortage, while a credit guarantees program is preferred when banks are undercapitalized...